Reforms in Information Communication Process and Field in Effective Management of Information Resource Centers - Baltabaevna, Xudaybergenova Marjan (International Journal on Human-Computing Studies, 2023)
the article talks about the culture of reading in information-library institutions, the processes of spiritual and educational education in information resource centers, and the specific features of spiritual and educational work. The research conducted by librarians, sociologists, psychologists and pedagogues of our country on issues of development of reading and reading culture among students and implementation of new reforms in this process has been analyzed.